14. Interdisciplinary Approach to Assessing the Acoustic Quality of Violins - Nauncef Alina Maria; Mihălcică Mircea; Roșca Ioan Călin; Gliga Vasile Ghiorghe; Marc Rodica; Mureșan Cristian (Sciendo, 2022)
The paper presents the interdisciplinary approach to assessing the acoustic quality of violins through a survey addressed to specialists in the field of music - instrumentalists, teachers, artists. Violins with modified geometric parameters in intermediate stages from a technological point of view were investigated, respectively unfinished violins (in white). The aim of the study was to classify the musical instruments heard according to five acoustic criteria considered relevant for violinists. Criteria such as: bright tone, clarity of sounds, warm/silky sound, amplitude of sounds and equal sound on all 4 strings were also established through a survey of artistic impressions among specialists, in a stage prior to the study presented in this article.